(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The exercise of citizenship behaviors and their impact on customer loyalty (An analytical study from the perspective of workers in the National Insurance Company). The Research aims to find out the degree of customers National Insurance company for customer citizenship behavior and its impact on the level oh loyalty from the perspective of employess in the company, as well as the statement of the differences in the answers of employees according to their personality traits. To achieve the goals of research has been the use of the questionnaire as a tool for the collection and distribution of data on a sample of (90) individuals, as was the use of statistical program (SPSS) in the process of statistical analysis methods (mean, standard deviation, Weight percentile, Alpha Cronbach, regression coefficient, ) the research found: Practiced behaviors of customers citizenship and moderately from the viewpoint of Alhaji, while the level of their loyalty highly. There is effect to the dimension of citizenship behaviors in enhancing customer loyalty to the company perspective of employees. Results did not show any differences in the trends of the sample surveyed about the effect of the exercise of citizenship behaviors in customer loyalty due to personality traits removal (Gender, Age, Marital Status, years of Service, Scientific Level, Jop Career).